A Feasibility Study to Investigate Chemogenetic Modulation of the Locus Coeruleus by Means of Single Unit Activity - Stevens, Latoya; Vonck, Kristl; Larsen, Lars Emil; Van Lysebettens, Wouter; Germonpré, Charlotte; Baekelandt, Veerle; Van den Haute, Chris; Carrette, Evelien; Wadman, Wytse Jan; Boon, Paul; Raedt, Robrecht (Frontiers in Neuroscience, 2020)
Aim: Selective chemogenetic modulation of locus coeruleus (LC) neurons would allow dedicated investigation of the role of the LC-NA pathway in brain excitability and disorders such as epilepsy. This study investigated the feasibility of an experimental set-up where chemogenetic modification of the brainstem locus coeruleus NA neurons is aimed at and followed by LC unit activity recording in response to clozapine. Methods: The LC of male Sprague-Dawley rats was injected with 10nl of adeno-associated viral vector AAV2/7-PRSx8-hM3Dq-mCherry (n=19, DREADD group) or AAV2/7-PRSx8-eGFP (n=13, Controls). Three weeks later, LC unit recordings were performed in anesthetized rats. We investigated whether clozapine, a drug known to bind to modified neurons expressing hM3Dq receptors, was able to increase the LC firing rate. Baseline unit activity was recorded followed by subsequent administration of 0.01 mg/kg and 0.1 mg/kg of clozapine in all rats. hM3Dq-mcherry expression levels were investigated using immunofluorescence staining of brainstem slices at the end of the experiment. Results: Unit recordings could be performed in 12 rats and in a total of 12 neurons (DREADDs: n=7, controls: n=5). Clozapine 0.01 mg/kg did not affect the mean firing rate of recorded LC-neurons; 0.1 mg/kg induced an increased firing rate, irrespective whether neurons were recorded from DREADD or control rats (p=0.006). Co-labeling of LC neurons and mCherry-tag showed that 20.6 ± 2.3% LC neurons expressed the hM3Dq receptor. Aspecific expression of hM3Dq-mCherry was also observed in non-LC neurons (26.0 ± 4.1%). Conclusions: LC unit recording is feasible in an experimental set-up following manipulations for DREADD induction. A relatively low transduction efficiency of the used AAV was found. In view of this finding, the effect of injected clozapine on LC-NA could not be investigated as a reliable outcome parameter for activation of chemogenetically modified LC neurons. The use of AAV2/7, a vector previously applied successfully to target dopaminergic neurons in the substantia nigra, leads to insufficient chemogenetic modification of the LC compared to transduction with AAV2/9.